The Wrong Kind of AI? Artificial Intelligence and the Future of Labor Demand - Daron Acemoglu; Pascual Restrepo (Institute of Labor Economics (IZA), 2019)
Artificial Intelligence is set to influence every aspect of our lives, not least the way production is organized. AI, as a technology platform, can automate tasks previously performed by labor or create new tasks and activities in which humans can be productively employed. Recent technological change has been biased towards automation, with insufficient focus on creating new tasks where labor can be productively employed. The consequences of this choice have been stagnating labor demand, declining labor share in national income, rising inequality and lower productivity growth. The current tendency is to develop AI in the direction of further automation, but this might mean missing out on the promise of the "right" kind of AI with better economic and social outcomes.
Keywords: J23; J24; 330; automation; artificial intelligence; jobs; inequality; innovation; labor demand; productivity; tasks; technology; wages